Effectiveness of an online intervention for parents/guardians of children aged 4–7 years who are concerned about their child’s emotional and behavioural development: protocol for an online randomised controlled trial (EMERGENT study) - Daniel Frings; Paula Reavey; Michael Leahy; Claudiu Herteliu; Jowinn Chew; Clare Allabyrne (BMJ Open)
Introduction The demand for resources to support emotional and behavioural development in early childhood is ever increasing. However, conventional interventions are lacking in resources and have significant barriers. The Embers the Dragon programme helps address the growing unmet need of children requiring support. The delivery of the current project seeks to help support parents, reduce the burden placed on pressed services (eg, Child and Adolescent Mental Health Services) and to help improve the emotional and behavioural development of children.Methods and analysis This project aims to investigate the efficacy and acceptability of Embers on parenting and children’s psychosocial outcomes. 364 parents/guardians of children aged between 4 and 7 will be recruited via the internet, schools and general practitioners (GPs). This is an online waitlist-controlled trial with three arms: (1) control arm, (2) access to Embers arm and (3) access to Embers+school. Participants will be randomised (1:1) into (1) or (2) to evaluate the use of Embers at home. To evaluate scalability in schools, (3) will be compared with (2), and (1) to test efficacy against treatment as usual (not receiving the intervention). Qualitative interviews will also be conducted. Primary outcomes are the Parental Self-efficacy Scale, Strengths and Difficulties Questionnaire and qualitative interviews. Outcomes will be compared between the three groups at baseline, 8, 16 and 24 weeks.Ethics and dissemination Ethical approval has been granted by the London South Bank University ethics panel (ETH2324-0004). To recruit via GPs, NHS ethical approval has been applied for, and the IRAS (331410) application is under consideration by the Central Bristol REC. The results of the project will be submitted for publication in a peer-reviewed journal. Parents/guardians will provide informed consent online prior to taking part in the study. For the interviews, assent will be taken from children by the researchers on the day.Trial registration number ISRCTN58327872